Deep-bed filters as post-treatment for ozonation in tertiary municipal wastewater treatment: impact of design and operation on treatment goals. Issue 1 (25th November 2020) - Sauter, Daniel; Dąbrowska, Agata; Bloch, Robert; Stapf, Michael; Miehe, Ulf; Sperlich, Alexander; Gnirss, Regina; Wintgens, Thomas
Abstract : The removal of organic contaminants during post-treatment with deep-bed filters after ozonation in tertiary municipal wastewater treatment can be optimised by the choice of filter material and contact time. Abstract : Ozonation followed by biological post-treatment is an established technology for abatement of organic micropollutants (OMP) from municipal wastewater. Although the necessity of biological post-treatment for oxidation by-product (OBP) removal is widely accepted, there is still discussion about the appropriate design and operation. The presented pilot-study investigates the impact of filter material and contact time on the removal efficiency of bulk organics, OMP, and OBP in three different deep-bed filters operated in parallel as post-treatment after ozonation (biological activated carbon (BAC) filter, dual-media filter sand/BAC and dual-media filter sand/anthracite). The use of BAC instead of non-adsorptive filter material resulted in higher removal of DOC and dissolved oxygen which indicates increased biological activity. Moreover, both BAC containing filters showed additional removal for a number of OMP even at high treated bed volumes of >50 000 whereas no removal was observed in the sand/anthracite filter. Analysis of N -nitrosodimethylamine (NDMA) and several carbonyl compounds revealed a clear formation of these biodegradable OBP during ozonation. A strong correlation was found between carbonyl formation and the specific ozone dose. Removal of OBP in the sand/BAC and the sand/anthracite filter was tested at different empty bed contact times (EBCT). While NDMA was efficiently removed independent of EBCT changes, there was a slightly negative impact of shorter EBCT on the reduction of carbonyl compounds. Furthermore, it was demonstrated that the integration of enhanced phosphorus removal into post-treatment is feasible with relatively low efforts by inline coagulant dosing (FeCl3 ) in the filter influent.